2011
DOI: 10.1002/jpln.201000050
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient status of apple leaves not affected by three years of irrigation using partial rootzone drying

Abstract: Partial rootzone drying (PRD) is a water‐saving irrigation technology that may affect apple (Malus domestica Borkh cv. Golden Delicious/Malling7)‐tree nutrition if applied for an extended period. The objective of this study was to test the hypothesis that long‐term application of PRD causes seasonal changes in macro‐ and micronutrients of apple leaves. The irrigation treatments were: (1) commercial irrigation as control (CI) and (2) PRD. After 3 years of evaluation, PRD irrigation had saved about 3240 m3 of wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Ca and Mg uptake is primarily through mass flow [10], therefore the plants irrigated at 100% and 75% ETc had the highest Ca and Mg concentrations in their leaves. It is because roots absorb more nutrients, especially calcium and magnesium, from the moisture-rich soil compared to dry soil as a result of more extensive root growth [46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca and Mg uptake is primarily through mass flow [10], therefore the plants irrigated at 100% and 75% ETc had the highest Ca and Mg concentrations in their leaves. It is because roots absorb more nutrients, especially calcium and magnesium, from the moisture-rich soil compared to dry soil as a result of more extensive root growth [46].…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have, however, reported that any reduction in irrigation amount does not hold any significant influence on the concentration of major nutrients like N, P, and K in leaves [8,9]. However, it is also seen that the literature on the influence of various irrigation regimes on leaf nutrients mainly focuses on calcium (Ca) and magnesium (Mg) because the moment of these nutrients in plants is primarily by mass flow [10] and therefore are most affected by irrigation.…”
Section: Introductionmentioning
confidence: 99%